Laser powder bed fusion of porous 304SS samples for use in developing oil impregnated ball bearings - Tafadzwa Mashayamombe; Stephen Matope (Discover Applied Sciences)
Abstract The ball bearing market is mature where there is a massive range of products available with new ones being developed all the time due to technological advancements. Additive Manufacturing (AM) provides a promising approach for developing oil-impregnated ball bearings. Oil impregnated bearings are critical for applications requiring smooth and low-friction motion. This study explores the feasibility of utilizing laser powder bed fusion (LPBF) technology to fabricate 304 stainless steel (304SS) samples with open pores, which can then be impregnated with a lubricant. To achieve this, 304SS powder was used, and optimum selective laser melting (SLM) printing parameters were altered to induce intentional pores. Initial screening of samples involved Archimedes density measurements and computed tomography (CT) scanning was conducted on a selected samples to assess their porosity levels. CT scan foam analysis results indicated a correlation between hatch spacing and porosity. Results revealed trends in cell volume and solidified scanning tracks thickness, indicating greater connectedness with larger pores. Synthesis of these findings could help in the development of efficient and reliable open pores that may find use in oil-impregnated self-lubricating ball bearings.